Cloud federation three-layer architecture: game-theoretic QoS modeling - Ma, Kun; Hu, Chuangyue; Zhang, Yuzhi; Ma, Fangchao; Wang, Xiaodong; Dang, Zhonghua; Xiao, Wenhong; Chen, Shuangxi (Dianxin Kexue, 2024)
Facing intense competition from large public cloud providers both domestically and internationally, the survival difficulties of small and medium cloud providers have increased. To address this, establishing a cloud federation based on cooperation has become a viable strategy for these providers. However, there is a complex interplay between pursuing individual maximum benefits and ensuring the overall quality of service（QoS） of the federation. A QoS based cloud federation model was proposed to address the above issues, covering a three-layer architecture of cloud computing. At the application to virtual layer, an innovative task allocation strategy based on the differential evolution（DE） algorithm was proposed, specifically designed to handle multi-QoS task distribution challenges. At the virtual to physical layer, a model for virtual machine migration that coexists with cooperation and competition was proposed,suitable for balancing energy consumption and QoS in a cloud federation game-theoretic computing e